A method for preparing a WC-Ni / Co hard alloy coating having a network metal phase structure

By using WC-Ni or WC-Co powder material with a mesh metal phase structure in the WC-Ni/Co coating, it is sprayed to the substrate using plasma spraying technology, which solves the problem of the existing coating keeping the hard phase WC solid during the spraying process, and achieves high hardness, low porosity and high bonding strength of the coating, significantly improving wear resistance.

CN118989346BActive Publication Date: 2025-04-22ZHUZHOU BODA HARD-FACING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411135732.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-04-22
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

During the spraying process, the existing WC-Ni/Co coatings have a lower flame temperature than the melting point of WC, causing the hard phase WC to remain solid and the bonding phase Ni/Co to melt, resulting in high porosity, low hardness, and poor bonding strength of the coating, which affects friction and wear resistance.

Method used

By mixing the nickel salt or cobalt salt with tungsten carbide in solution, reacting at 80-100°C, pH=8-12, and heat treatment is performed to obtain a WC-Ni or WC-Co powder material with a mesh metal phase structure. The material is sprayed to the substrate by plasma spraying technology to form a coating with improved metal phase distribution and increased bond strength.

Benefits of technology

The metal phase Ni or Co has a mesh structure distribution, improves the microstructure of the coating, improves the fracture toughness, hardness and bonding strength of the coating, and significantly improves the wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118989346B_ABST
    Figure CN118989346B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a WC-Ni / Co cemented carbide coating with a network metal phase structure, and relates to the technical field of new material preparation. The present invention first coats a uniform and dense layer of metal Ni or Co on the surface of WC ceramic particles, and then uses plasma spraying technology to prepare the coated WC-Ni / Co powder into a WC-Ni / Co cemented carbide coating, which effectively solves the problem of high-temperature decomposition and decarburization of the hard phase WC when the plasma spraying technology is used to prepare the WC-based cemented carbide coating, and successfully prepares a WC-Ni / Co cemented carbide coating with a network structure distribution of the metal phase Ni or Co. The coating obtained by the present invention has the advantages of uniform metal phase distribution, high fracture toughness, low porosity, high hardness, good bonding strength and excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new material preparation, and in particular to a method for preparing a WC-Ni / Co hard alloy coating with a network metal phase structure. Background Art

[0002] Friction and wear are the main factors that cause the performance, life and reliability of key equipment components to decline, and have become an important bottleneck restricting their development. Designing coatings on the surfaces of key equipment components can not only significantly extend their service life, but also improve the accuracy and reliability of the entire set of equipment, which has important economic value and social significance.

[0003] The coating design mainly includes coating materials, coating equipment and coating preparation process. WC-Ni / Co metal ceramic coating material is the most widely used coating material in the wear-resistant field due to its high hardness, wear resistance and high temperature resistance. Traditional WC-Ni / Co materials are made of WC powder, Ni or Co powder as raw materials, and are prepared through wet grinding, spray granulation, sintering, screening and other processes. The metal phase Ni or Co is dispersed in the hard phase WC. The screening particle size of the material is in the range of 5-53 microns, and the microscopic morphology is spherical. In terms of coating equipment and preparation process, the flame temperature of the supersonic flame spraying equipment is between 2700℃-2850℃, which is slightly lower than the melting point of the hard phase WC ceramic at 2870℃. It will not cause WC decomposition due to high temperature during the spraying process. In addition, the supersonic flame spraying technology has the characteristics of easy operation and high particle flight speed. It is currently the most important method for preparing WC-Ni / Co spherical powder into cemented carbide wear-resistant coatings.

[0004] The metal phase of the traditional WC-Ni / Co coating prepared by supersonic flame spraying technology is blocky and dispersed, such as Figure 5 , Figure 6 , which will lead to problems such as uneven hardness distribution and poor fracture toughness in the coating; in addition, since the flame temperature of the supersonic flame spraying equipment is lower than the melting point of the hard phase WC, only the binding phase Ni / Co in the WC-Ni / Co spherical powder melts during the coating preparation process, and the hard phase WC remains in a solid state, which will cause defects such as high porosity, low hardness, and poor bonding strength in the coating. These properties directly affect the friction and wear resistance of the coating.

[0005] Improving the metal phase distribution in the coating and increasing the temperature of the spraying flame are effective methods to improve the wear resistance of WC-Ni / Co cemented carbide coatings. Plasma spraying technology uses plasma flame flow as a heat source, and the working temperature is as high as 6000℃ or above. After the spraying powder is pushed into the plasma jet by the powder feeding airflow, it is quickly heated to a molten state and hits the surface of the workpiece at a high speed of 300-400m / s, forming a firmly attached and dense plasma spray coating. However, plasma spraying technology is currently unable to achieve the preparation of conventional WC-Ni / Co metal ceramic coatings. The main obstacle is that the temperature of the plasma spraying flame flow (above 6000℃) is much higher than the melting point of WC ceramics (2870℃). During the spraying process, the hard phase WC will undergo high-temperature decomposition in the plasma flame flow.

[0006] Therefore, it has become an urgent problem to prepare a WC-based cemented carbide material that can improve the metal phase distribution and is suitable for the high temperature of plasma spraying flame. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a WC-Ni / Co hard alloy coating with a network metal phase structure to solve the problems existing in the above-mentioned prior art.

[0008] To achieve the above object, the present invention provides the following solutions:

[0009] The present invention provides a method for preparing a WC-Ni or WC-Co powder material having a network metal phase structure, comprising the following steps:

[0010] Nickel salt or cobalt salt is mixed with tungsten carbide in a solution, reacted at 80-100°C and pH=8-12 in the presence of a complexing agent, a stabilizer and a reducing agent, and then heat treated to obtain the WC-Ni or WC-Co powder material with a network metal phase structure.

[0011] As a further preferred embodiment of the present invention, the temperature of the heat treatment is 1100°C-1300°C.

[0012] As a further preferred embodiment of the present invention, the tungsten carbide is soaked in a citric acid solution; the preferred soaking time is 30-60 minutes.

[0013] In the present invention, the purpose of soaking tungsten carbide in citric acid solution is to remove oil and dust that may be adsorbed on its surface. The preferred citric acid concentration is 6.0 g / L.

[0014] As a further preferred embodiment of the present invention, the complexing agent is methyl cellulose; the stabilizer is boric acid; and the reducing agent is sodium hypophosphite.

[0015] As a further preferred embodiment of the present invention, the tungsten carbide has a Fisher grain size of 10 μm-50 μm.

[0016] As a further preferred embodiment of the present invention, the nickel salt is nickel acetate (C4H5NiO4·4H2O), and the cobalt salt is cobalt acetate (C4H6CoO4·4H2O).

[0017] As a further preferred embodiment of the present invention, the powder heating treatment method is a vertical medium frequency (150-10000 Hz) induction tube furnace protected by argon gas.

[0018] As a further preferred embodiment of the present invention, the preparation method specifically comprises the following steps: mixing nickel salt or cobalt salt with a complexing agent and a stabilizer in a solvent, adjusting the system pH to 8-12 and the temperature to 80-100°C, then adding tungsten carbide and a reducing agent, and then continuing to react at a pH of 8-12 and a temperature of 80-100°C for 30-120 minutes, and then heat-treating the solid obtained by the reaction to obtain the WC-Ni or WC-Co material having a network metal phase structure.

[0019] As a further preferred embodiment of the present invention, before the heat treatment, the solid obtained by the reaction is further dried and ground, and the preferred drying temperature is 60°C-100°C.

[0020] As a further preferred embodiment of the present invention, the mass ratio of the nickel salt or cobalt salt to the complexing agent, stabilizer, tungsten carbide and reducing agent is 280g-420g: 90g-130g: 2.5mg-3.5mg: 350g-650g: 80g-110g.

[0021] Taking the preparation of 1L solution as an example, the amount of nickel acetate or cobalt acetate added is 280g-420g, the amount of boric acid added is 2.5mg-3.5mg, the amount of methyl cellulose added is 90g-130g, and the amount of deionized water added is 1000mL: the mass of WC powder added to every 1000mL of chemical plating solution is 350g-650g, and the amount of sodium hypophosphite added is 80g-110g.

[0022] The present invention also provides a WC-Ni or WC-Co coating with a mesh metal phase structure, which is obtained by spraying the WC-Ni or WC-Co material onto a substrate using a plasma spraying technique.

[0023] As a further preferred embodiment of the present invention, the process parameters of the plasma spraying technology are as follows:

[0024] Current 300-600A, argon flow 70-90NLPM, hydrogen flow 2-6NLPM, carrier gas flow 12-20NLPM, powder feeding amount 65-90g / min, spraying distance 90-120mm, gun speed 20-40mm / s.

[0025] As a further preference of the present invention, an annealing treatment is further included for the prepared coating, wherein the preferred annealing temperature is 600° C.-900° C. and the holding time is 1 h-2 h.

[0026] The present invention also provides a coating device, the surface of which is sprayed with the WC-Ni or WC-Co coating with a mesh metal phase structure.

[0027] In the present invention, it is preferred that the powder flows from top to bottom through the tube furnace through a vertical medium frequency induction tube furnace protected by argon gas, which can avoid both powder oxidation and the problem of bonding and agglomeration during heat treatment of traditional boat-type metal ceramic powders. More preferably, the powder flow rate through the tube furnace is 50g / min-150g / min.

[0028] The present invention firstly coats a uniform and dense layer of metal Ni or Co on the surface of WC ceramic particles, then uses plasma spraying technology to further prepare the coated WC-Ni / Co powder into a WC-Ni or WC-Co coating with a network metal phase structure, and finally anneals the coating.

[0029] The coating of the WC ceramic particles with metal Ni or Co on the surface of the WC ceramic particles can not only effectively solve the problem of WC decomposition caused by excessively high flame flow temperature, but also make the metal phase in the coating distributed in a network structure, thereby improving the microstructure of the coating.

[0030] The process parameters for preparing the mesh metal phase structure coating by plasma spraying technology in the present invention are shown in Table 1.

[0031] Table 1

[0032]

[0033] The present invention discloses the following technical effects:

[0034] 1. The raw materials used in the present invention are harmless to the human body and environmentally friendly, and there is no need to activate or sensitize the WC powder before coating, and the invention has the characteristics of low cost, no pollution, and simple process.

[0035] 2. The present invention heat treats the coated powder to improve the compactness of the coating layer metal Ni or Co and the bonding strength with the coated WC.

[0036] 3. The present invention uses WC powder coated with metal Ni or Co as raw material, solves the problem of high-temperature decomposition and decarburization of the hard phase WC when preparing WC-based cemented carbide coatings using plasma spraying technology, and successfully prepares WC-Ni / Co cemented carbide coatings with metal phase Ni or Co presenting a network structure distribution.

[0037] 4. The present invention performs annealing treatment on the prepared coating, which can eliminate the thermal stress of the coating generated by rapid cooling during the plasma spraying process.

[0038] 5. The WC-Ni / Co coating prepared by the present invention utilizes the high temperature of the plasma spraying flame flow and designs the metal phase distribution of the network structure, and has the advantages of uniform metal phase distribution, high fracture toughness, low porosity, high hardness, good bonding strength and excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 (a) is a SEM electron microscope image of the cross section of the WC-Ni powder obtained in Example 1 and (b) is a SEM electron microscope image of the cross section of the WC-Ni coating obtained.

[0041] Figure 2 (a) is a SEM electron microscope image of the WC-Co powder obtained in Example 2 and (b) is a SEM electron microscope image of the cross section of the obtained WC-Co coating.

[0042] Figure 3 (a) The XRD pattern and (b) cross-sectional SEM image of the WC-Ni coating obtained in Example 3.

[0043] Figure 4 (a) is a SEM electron microscope image of the WC-Co powder obtained in Example 4 and (b) is a SEM electron microscope image of the cross section of the obtained WC-Co coating.

[0044] Figure 5 The SEM image (a) of the conventional agglomerated sintered powder obtained in Comparative Example 1 and the SEM image (b) of the cross section of the WC-Ni coating obtained by supersonic flame spraying technology.

[0045] Figure 6 The metallographic image (a) of the cross section of the conventional agglomerated sintered powder obtained in Comparative Example 2 and the SEM electron microscope image (b) of the cross section of the WC-Co coating obtained by supersonic flame spraying technology. DETAILED DESCRIPTION

[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0047] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0051] Example 1

[0052] (1) 280 g of nickel acetate, 90 g of methyl cellulose and 2.5 mg of boric acid were dissolved in 1 L of deionized water. The pH value of the resulting solution was adjusted to 8 using NaOH. The prepared chemical plating solution was heated using an electric constant temperature water bath at a water bath temperature of 80° C. and stirred using a powerful electric stirrer equipped with a polytetrafluoroethylene stirring rod.

[0053] (2) 350 g of WC with a Fisher particle size of 10 μm was soaked in citric acid (6.0 g / L) for 30 min, filtered with filter paper and washed with deionized water three times; then the WC was added to the chemical plating solution prepared in step (1), and 80 g of sodium hypophosphite was slowly added. The reaction time was maintained for 30 min, during which the pH value of the solution was always controlled to be 8.

[0054] (3) filtering the solution after the reaction in step (2), adding deionized water to the obtained filter residue, stirring, cleaning, and filtering, and repeating this process 5 times; then drying the obtained powder at 60° C. in a drying oven, and finally crushing it in a grinder to obtain metal Ni-coated WC powder.

[0055] (4) The metal Ni-coated WC powder prepared in step (3) was poured into the upper feed port of an argon-protected vertical medium-frequency induction tube furnace at a flow rate of 50 g / min, and the furnace temperature was 1100° C. to obtain WC-Ni powder.

[0056] (5) Use 60 mesh corundum powder to sandblast the surface of 45# steel, then rinse it with high-pressure deionized water, and finally blow dry the surface of 45# steel with compressed air; use plasma spraying equipment to spray WC-Ni powder on the surface of 45# steel to prepare the coating. The spraying process parameters are: current 300A, argon flow rate 70NLPM, hydrogen flow rate 2NLPM, carrier gas flow rate 12NLPM, powder feeding amount 65g / min, spraying distance 90mm, and gun speed 20mm / s.

[0057] (6) The prepared WC-Ni coating was annealed in a vacuum furnace at a temperature of 600°C and a holding time of 2 h.

[0058] SEM electron micrograph of the cross section of the WC-Ni powder prepared in Example 1 (a) and SEM electron micrograph of the obtained WC-Ni coating (b).

[0059] Example 2

[0060] (1) 320 g of cobalt acetate, 100 g of methyl cellulose, and 2.7 mg of boric acid were dissolved in 1 L of deionized water. The pH value of the resulting solution was adjusted to 9 using NaOH. The prepared chemical plating solution was heated using an electric constant temperature water bath at a water bath temperature of 85° C. and stirred using a powerful electric stirrer equipped with a polytetrafluoroethylene stirring rod.

[0061] (2) 420 g of WC with a Fisher particle size of 20 μm was soaked in citric acid (6.0 g / L) for 40 min, filtered with filter paper and washed three times with deionized water; then the WC was added to the chemical plating solution prepared in step (1), and 90 g of sodium hypophosphite was slowly added. The reaction time was maintained for 50 min, during which the pH value of the solution was always controlled to be 9.

[0062] (3) Filter the solution after the reaction in step (2), add deionized water to the obtained filter residue, stir, wash and filter, and repeat this process 5 times; then use a drying oven to dry the obtained powder at 70° C., and finally use a grinder to crush it to obtain metal Co-coated WC powder.

[0063] (4) The metal Co-coated WC powder prepared in step (3) was poured into the upper feed port of an argon-protected vertical medium-frequency induction tube furnace at a flow rate of 80 g / min, and the furnace temperature was 1150° C. to obtain WC-Co powder.

[0064] (5) Use 60 mesh corundum powder to sandblast the surface of 45# steel, then rinse it with high-pressure deionized water, and finally blow dry the surface of 45# steel with compressed air; use plasma spraying equipment to spray WC-Co powder on the surface of 45# steel to prepare the coating. The spraying process parameters are: current 380A, argon flow rate 75NLPM, hydrogen flow rate 3NLPM, carrier gas flow rate 14NLPM, powder feeding amount 72g / min, spraying distance 95mm, and gun speed 28mm / s.

[0065] (6) The prepared WC-Co coating was annealed in a vacuum furnace at a temperature of 900°C and a holding time of 1 h.

[0066] Figure 2 (a) is a SEM electron microscope image of the WC-Co powder obtained in Example 2 and (b) is a SEM electron microscope image of the WC-Co coating obtained.

[0067] Example 3

[0068] (1) 350 g of nickel acetate, 110 g of methyl cellulose, and 2.9 mg of boric acid were dissolved in 1 L of deionized water. The pH value of the resulting solution was adjusted to 10 with NaOH. The prepared chemical plating solution was heated in an electric constant temperature water bath at a water bath temperature of 100° C. and stirred in a powerful electric stirrer equipped with a polytetrafluoroethylene stirring rod.

[0069] (2) 500 g of WC with a Fisher particle size of 30 μm was soaked in citric acid (6.0 g / L) for 45 min, filtered with filter paper and washed with deionized water three times; then the WC was added to the chemical plating solution prepared in step (1), and 100 g of sodium hypophosphite was slowly added. The reaction time was maintained for 70 min, during which the pH value of the solution was always controlled to be 10.

[0070] (3) filtering the solution after the reaction in step (2), adding deionized water to the obtained filter residue, stirring, cleaning, and filtering, and repeating this process 5 times; then drying the obtained powder at 80° C. in a drying oven, and finally crushing it in a grinder to obtain metal Ni-coated WC powder.

[0071] (4) The metal Ni-coated WC powder prepared in step (3) is poured into the upper feed port of an argon-protected vertical medium-frequency induction tube furnace at a flow rate of 110 g / min, and the furnace temperature is 1200° C. to obtain WC-Ni powder.

[0072] (5) Use 60 mesh corundum powder to sandblast the surface of 45# steel, then rinse it with high-pressure deionized water, and finally blow dry the surface of 45# steel with compressed air; use plasma spraying equipment to spray WC-Ni powder on the surface of 45# steel to prepare the coating. The spraying process parameters are: current 450A, argon flow rate 82NLPM, hydrogen flow rate 4NLPM, carrier gas flow rate 16NLPM, powder feeding amount 78g / min, spraying distance 100mm, and gun speed 32mm / s.

[0073] (6) The prepared WC-Ni coating was annealed in a vacuum furnace at a temperature of 700°C and a holding time of 100 min.

[0074] Figure 3 (a) XRD pattern and (b) SEM electron microscope image of the WC-Ni coating obtained in Example 3.

[0075] Example 4

[0076] (1) 380 g of cobalt acetate, 120 g of methyl cellulose, and 3.2 mg of boric acid were dissolved in 1 L of deionized water. The pH value of the resulting solution was adjusted to 11 using NaOH. The prepared chemical plating solution was heated in an electric constant temperature water bath at a water bath temperature of 90° C. and stirred using a powerful electric stirrer equipped with a polytetrafluoroethylene stirring rod.

[0077] (2) 580 g of WC with a Fisher particle size of 40 μm was soaked in citric acid (6.0 g / L) for 50 min, filtered with filter paper and washed three times with deionized water; then the WC was added to the chemical plating solution prepared in step (1), and 105 g of sodium hypophosphite was slowly added. The reaction time was maintained for 90 min, during which the pH value of the solution was always controlled to be 11.

[0078] (3) Filter the solution after the reaction in step (2), add deionized water to the obtained filter residue, stir, wash and filter, and repeat this process 5 times; then use a drying oven to dry the obtained powder at 90° C., and finally use a grinder to crush it to obtain metal Co-coated WC powder.

[0079] (4) The metal Co-coated WC powder prepared in step (3) was poured into the upper feed port of an argon-protected vertical medium-frequency induction tube furnace at a flow rate of 130 g / min, and the furnace temperature was 1250° C. to obtain WC-Co powder.

[0080] (5) Use 60 mesh corundum powder to sandblast the surface of 45# steel, then rinse it with high-pressure deionized water, and finally blow dry the surface of 45# steel with compressed air; use plasma spraying equipment to spray WC-Co powder on the surface of 45# steel to prepare the coating. The spraying process parameters are: current 520A, argon flow rate 85NLPM, hydrogen flow rate 5NLPM, carrier gas flow rate 18NLPM, powder feeding amount 85g / min, spraying distance 110mm, and gun speed 36mm / s.

[0081] (6) The prepared WC-Ni coating was annealed in a vacuum furnace at a temperature of 800°C and a holding time of 90 min.

[0082] Figure 4 (a) is a SEM electron microscope image of the WC-Co powder obtained in Example 4 and (b) is a SEM electron microscope image of the cross section of the obtained WC-Co coating.

[0083] Comparative Example 1

[0084] The preparation steps of traditional WC-12Ni cemented carbide coating are as follows:

[0085] (1) The material WC-12Ni was weighed according to its nominal mass percentage, wherein the mass fraction of WC was 88%, the mass fraction of metal Ni was 12%, and PEG was used as a binder, and its addition amount was 1.0% of the total mass.

[0086] (2) Pour the prepared materials into a ball mill, use deionized water as the wet grinding medium, control the ball-to-material ratio within the range of 2.5:1, and the ball milling time is 72 hours.

[0087] (3) The wet-milled slurry was spray-granulated using a spray drying tower, wherein the air outlet temperature was 100° C. and the atomizing disk rotation speed was 12,000 rpm, to obtain a spherical mixture for use.

[0088] (4) The spherical mixture is placed in a vacuum furnace or a molybdenum wire furnace and sintered at 1150°C for 4 hours.

[0089] (5) Use an ultrasonic sieving machine or an air flow classifier to sieve the sintered powder into a particle size range of 5 μm-53 μm.

[0090] (6) The prepared powder was sprayed into a coating using a supersonic flame spraying device, wherein the kerosene flow rate was 22 L / h and the oxygen flow rate was 48 m / h.3 / h, powder feeding rate is 60g / min, and spraying distance is 330mm.

[0091] Figure 5 The SEM electron microscope image (a) of the traditional agglomerated sintered powder obtained in Comparative Example 1 and the SEM electron microscope image (b) of the WC-Ni coating obtained by supersonic flame spraying technology.

[0092] Comparative Example 2

[0093] The preparation steps of traditional WC-12Co cemented carbide coating are as follows:

[0094] (1) The material WC-12Co is weighed according to its nominal mass percentage, where the mass fraction of WC is 88% and the mass fraction of metal Co is 12%. PVA is used as a binder and its addition amount is 1.0% of the total mass.

[0095] (2) Pour the prepared materials into a ball mill, use deionized water as the wet grinding medium, control the ball-to-material ratio within the range of 2.5:1, and the ball milling time is 72 hours.

[0096] (3) The wet-milled slurry was spray-granulated using a spray drying tower, wherein the air outlet temperature was 100° C. and the atomizing disk rotation speed was 12,000 rpm, to obtain a spherical mixture for use.

[0097] (4) The spherical mixture is placed in a vacuum furnace or a molybdenum wire furnace and sintered at 1250°C for 4 hours.

[0098] (5) Use an ultrasonic sieving machine or an air flow classifier to sieve the sintered powder into a particle size range of 5 μm-53 μm.

[0099] (6) The prepared powder was sprayed into a coating using a supersonic flame spraying device, wherein the kerosene flow rate was 22 L / h and the oxygen flow rate was 48 m / h. 3 / h, powder feeding rate is 60g / min, and spraying distance is 330mm.

[0100] Figure 6 The metallographic image (a) of the cross section of the conventional agglomerated sintered powder obtained in Comparative Example 2 and the SEM electron microscope image (b) of the WC-Co coating obtained by supersonic flame spraying technology.

[0101] It can be seen from the XRD and SEM images of the WC-Ni or WC-Co powder and the corresponding coating prepared by the method of the present invention that the method of the present invention can successfully prepare a WC-Ni / Co cemented carbide coating with a network structure distribution of the metal phase Ni or Co.

[0102] The porosity, microhardness, fracture toughness of the coating and the bonding strength between the coating and the substrate were tested in accordance with GB / T13298-2015, GB / T9790-2021, GB / T 21143-2014 and ASTM C633-2001 respectively.

[0103] The performance comparison results of the WC-Ni or WC-Co hard alloy coatings prepared in Examples 1-4 and the hard alloy coatings prepared in Comparative Examples 1-2 are shown in Table 2.

[0104] Table 2

[0105]

[0106]

[0107] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a WC-Ni / Co hard alloy coating having a network metal phase structure, characterized in that: Mixing nickel salt or cobalt salt with a complexing agent and a stabilizer in a solvent, then adding tungsten carbide and a reducing agent, reacting at a pH of 8-12 and a temperature of 80-120° C., and heat-treating the solid obtained by the reaction to obtain a WC-Ni or WC-Co powder material; Spraying WC-Ni or WC-Co powder material onto a substrate by plasma spraying to obtain a coating, and then performing vacuum annealing on the coating; The complexing agent is methyl cellulose; the stabilizer is boric acid; the reducing agent is sodium hypophosphite; The mass ratio of the nickel salt or cobalt salt to the complexing agent, stabilizer, tungsten carbide and reducing agent is 280g-420g: 90g-130g: 2.5mg-3.5mg: 350g-650g: 80g-110g; The process parameters of the plasma spraying are as follows: current 300-600A, argon flow rate 70-90NLPM, hydrogen flow rate 2-6NLPM, carrier gas flow rate 12-20NLPM, powder feeding amount 65-90g / min, spraying distance 90-120mm, gun speed 20-40mm / s; the temperature of the vacuum annealing treatment of the coating is 600℃-900℃, and the insulation time is 1h-2h.

2. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 1100°C-1300°C.

3. The preparation method according to claim 1, characterized in that: The tungsten carbide has a particle size of 10 μm to 50 μm; The tungsten carbide is soaked in a citric acid solution.

4. The preparation method according to claim 1, characterized in that: The nickel salt is nickel acetate, and the cobalt salt is cobalt acetate.

Citation Information

Patent Citations

  • Metal-coated WC hard alloy coating and preparation method thereof

    CN115717227A